Effectiveness of Coaching and Mentoring Models to Enhance P5 Implementation in Primary Schools - Darmin; Yahya, Muhammad; Yahya, Patta (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Implementing the Pancasila Student Profile (Proyek Penguatan Profil Pelajar Pancasila, P5) in Indonesian primary schools is a recent curriculum initiative aimed at strengthening student character and competencies. However, many primary schools face challenges in effectively integrating P5 due to limited teacher understanding of character-based pedagogy and lack of contextual learning tools. This case study examines how a structured coaching and mentoring model can enhance P5 implementation at a public primary school in Makassar, Indonesia. A qualitative approach was used, including interviews with five teachers and two school leaders, and classroom observations of P5 project activities. The results indicate that the coaching and mentoring model significantly improved teachers’ pedagogical practices and confidence in integrating Pancasila values into lessons. Teachers reported that regular coaching sessions helped them reflect on and refine their instructional strategies, while mentoring by experienced educators provided practical guidance and moral support. School leaders observed increased student engagement and more authentic character development during P5 projects. The findings align with recent literature suggesting that ongoing coaching and peer mentoring are effective forms of teacher professional development for character education. This study contributes to understanding how collaborative, reflective professional learning can strengthen curriculum reforms. It highlights the importance of sustained teacher support through coaching and mentoring in successfully translating the P5 character education goals into classroom practice. The paper discusses implications for educators and policymakers seeking to embed character education in primary education and offers recommendations for scaling such coaching-mentoring models.